2012
DOI: 10.5665/sleep.2244
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Nocturnal Awakenings in a Case Series of Treatment-Seeking Chronic Insomnia Patients: A Pilot Study of Subjective and Objective Causes

Abstract: Among patients with insomnia with no classic sleep breathing symptoms and therefore low probability of a sleep breathing disorder, most of their awakenings were precipitated by a medical condition (sleep disordered breathing), which contrasted sharply with their perceptions about their awakenings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…In a metaanalysis of CBTi in comorbid medical and psychiatric disorders, only 36% of patients were in remission after treatment [15]. Supporting the role that Boccult^sleep disordered breathing is present in many patients with refractory insomnia is an article by Krakow et al that reported 90% of nocturnal awakenings in patients with chronic insomnia only (no suspicion of OSA) were due to respiratory events [16]. Clearly, a higher clinical suspicion for COMISA is required in patients with sleep disturbances as their presentation is not always classic.…”
mentioning
confidence: 99%
“…In a metaanalysis of CBTi in comorbid medical and psychiatric disorders, only 36% of patients were in remission after treatment [15]. Supporting the role that Boccult^sleep disordered breathing is present in many patients with refractory insomnia is an article by Krakow et al that reported 90% of nocturnal awakenings in patients with chronic insomnia only (no suspicion of OSA) were due to respiratory events [16]. Clearly, a higher clinical suspicion for COMISA is required in patients with sleep disturbances as their presentation is not always classic.…”
mentioning
confidence: 99%
“…70 Although difficulty maintaining sleep is the most frequent insomnia complaint among adults with comorbid insomnia and SDB, other insomnia complaints are common; 71 in our sample, we found a wide variety of insomnia complaints among the women with SDB and insomnia. The causal pathway for the insomnia/SDB combination is likely bidirectional: although the frequent awakenings from SDB events may induce insomnia, 72 the fragmented and ''light'' sleep that is characteristic of insomnia may predispose to SDB. 21 Our sample did not have adequate statistical power to examine the sleep hygiene behaviors of women with both insomnia and SDB.…”
Section: Discussionmentioning
confidence: 99%
“…The danger of OSA going undetected among insomnia patients has been previously documented. Krakow and colleagues found that in patients endorsing insomnia but no sleep-disordered breathing (SDB) symptoms, most nighttime awakenings actually followed respiratory events, unbeknownst to the patient, 63 and 50% of the sample met criteria for OSA. Fung et al found that almost half of study participants with insomnia suffered from occult SDB (AHI ≥ 15), and the presence of excessive daytime sleepiness was the distinguishing factor between occult and nonexistent SDB.…”
Section: "Mild Insomnia" Symptom Cluster Profilementioning
confidence: 99%